Relapsed Mantle Cell Lymphoma Presenting as “Sister Mary Joseph Nodule” - Jennifer E. Vaughn; Ajay K. Gopal (Case Reports in Medicine)
The finding of umbilical metastasis has historically been called a “Sister Mary Joseph Nodule”. A few case reports of lymphoma presenting in this manner have been documented. We report a case of relapsed mantle cell lymphoma (MCL) presenting as a Sister Mary Joseph's nodule. Although the few reports of lymphoma exhibiting umbilical metastasis suggest that patients may still expect a reasonable response to chemotherapy, this patient experienced multiple relapses, despite aggressive chemotherapy regimens. This clinical course is characteristic of the mantle cell form of non-hodgkin's lymphoma and illustrates a need to seek out more effective therapies.